A Disposable Dispensing Valve for Non-Contact Microliter Applications in a 96-Well Plate Format - Sabrina Kartmann (Micromachines, 2015)
We present a miniaturized, disposable, normally-closed electromagnetic dispensing valve for the microliter range to process 96-well plates. The novel injection-molded valve is designed to fit into a 9 mm grid to realize an eight channel dispensing head, enabling the serial processing of well plates row-by-row. The presented dispensing valve design originates from a miniaturization study of a previously developed functional model. The outer diameter of the valve, including all actuating components, was reduced by 8 mm to an overall diameter of 8.5 mm without compromising the performance. Additionally, the actuation current of the valve could be reduced to 5 A. The valve is characterized for a volume range between 840 nL and 5.3 μL. The performance of the injection molded valve is competitive to commercially available dispensing valves, featuring the advantages of low fabrication costs, disposability, low mounting size, easy handling, and super silent actuation.